Reorientasi Asas Kebebasan Berkontrak dalam Perjanjian Baku di Indonesia dalam mewujudkan Keadilan Kontraktual Berbasis Asas Proporsionalitas - Suparwi Suparwi; Firstnandiar Glica Aini Suniaprily; Hanuring Ayu Ardhani Putri; Nourma Dewi; Adhy Nugraha (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The principle of freedom of contract, as stipulated in Article 1338 of the Civil Code, forms the legal foundation of contracts in Indonesia. In practice, the proliferation of standard-form contracts has led to this principle often being merely formal in nature, as one party lacks adequate opportunity to negotiate the contract’s terms. This study aims to analyze the shift in the meaning of the principle of freedom of contract in standard-form contracts and to formulate a reorientation model focused on contractual justice. The study employs a normative legal methodology using legislative, conceptual, and case-based approaches. The results of the study indicate that the application of the principle of freedom of contract in standard form contracts has shifted from the concept of absolute freedom toward a freedom limited by the principles of balance, good faith, and protection of the party with weaker bargaining power. Therefore, a reorientation of the principle of freedom of contract is necessary through the application of the principle of proportionality as an instrument to create contractual relationships that are fair, balanced, and provide legal certainty.